Sustainable Livelihood Strategies: How Urban Community Resilient Towards Disaster? - Navila Ulfi Fauziyanti; Dyah Rahmawati Hizbaron (Faculty of Geography, Universitas Gadjah Mada, 2020)
It has been more than a decade after 5.9 SR earthquakes hit one of the most destructed area Tembi Hamlet, Bantul District, Yogyakarta Province. Amidst the wreaking havoc, the area gained its resilient in no time. This research, aimed to 1) explore what are the factors influential towards local resilient, especially micro-small-medium enterprises; and 2) analyze strategies to tackle disaster. It employed mix method, while the key questions were developed using “Sustainable Livelihood Approach” by DFID, geared with “Pentagram Asset” mapping for each spatial and temporal unit. The result revealed that 1) the micro-small-medium enterprises in urban area are resilient towards earthquake due to fair physical, natural and financial assets management and abundant social, human and political assets. These assets have created enabling environment towards behavioral change of urban society; 2) Despite various livelihood strategies existed in urban areas, the research highlighted three types of livelihood strategies within disaster risk management perspective, i.e. survival (disaster), consolidation by no-change plan mechanism and accumulation strategies by change plan mechanism (post disaster). Critically, pentagram assessment is able to identify feasible local assets and activities, however it left the policy, institution, interaction and multi sector aspects from the spotlight. Herewith, the research proposes evaluation scan to rethinking sustainable livelihood approach within disaster risk management by adding these aspects into the observation. It also revealed that local autonomous initiatives to extend urban based economic activities and supported by abundant political interest play pivotal role in disaster management at developing countries.